Public Private Partnerships Renegotiations in Transportation Case Studies from Portugal - Oliveira Cruz, Carlos; Miranda Sarmento, Joaquim (Cham : Springer International Publishing : Imprint: Springer, 2022)
There is a growing interest in Public-Private Partnerships (PPPs), particularly in infrastructure and public services. Under the scope of PPPs, renegotiations are becoming more relevant, as empirical evidence suggests that most PPP projects are inevitably renegotiated, i.e., the original contract needs to be adapted to new and unforeseen circumstances. Renegotiations have a substantial impact on the contract and performance of a PPP and usually represent significant costs for users and taxpayers. However, very little is known about the management and, mainly, the process of renegotiating that will, very likely, occur. This book provides a set of case-studies of PPP renegotiations in the transport sector. The authors illustrate the Portuguese experience, a country that has been using PPP extensively, particularly in transport. The case studies provide an extensive and detailed analysis on each aspect of the project and the renegotiation. What drives renegotiations? Why are some projects more renegotiated than others? What are the results? How can the performance of renegotiation processes be improved? These and other questions provide the basis for the discussions in this book. The novelty and value of the book come mainly from the extent of information available. Each case-study deals with these questions in much more detail than what is common in the case-studies approach. .
Chapter 1. Introduction -- Chapter 2. The Portuguese Experience of Public Private Partnerships and Renegotiations -- Chapter 3. Fertagus (trains) -- Chapter 4. Lusoponte (bridge) -- Chapter 5. Metro Sul do Tejo (light rail) -- Chapter 6. AEA Highway (road sector) -- Chapter 7. Litoral Centro - Brisal -- Chapter 8. Douro Litoral (road sector) -- Chapter 9. SCUTs -- Chapter 10. Troika Renegotiations.
Keywords: Public administration; Microeconomics; Finance, Public; Transportation; Public Administration; Microeconomics; Public Finance; Transportation Economics